Effect of Neem Products on Seed Quality Parameters of Soybean during Storage - ANIL K. NAKKA; SANDEEP KUMAR LAL; A. GAUR; C. DEVAKUMAR; O.K. SHARMA (Seed Research, 2026)
Seeds of three soybean cultivars namely, PK-472, PS-564 and PS-1024 were obtained from JNKVV, Jabalpur and multiplied at IARI, New Delhi. The freshly harvested seeds were sun-dried for 2-3 days to bring down their moisture content to the level of 8 per cent and used in the present studies to observe the relative efficacy of neem products on seed storability. These seed lots were separately treated with tetra methyl thiuram disulphide (TMTD @ 0.3%) and with 0.25 and 0.50 per cent of Hexane extract of seed kernel (HESK), Methanol extract of seed kernel (MESK), Chloroform extract of seed coat and Methanol extract of seed coat (MESC) of neem seed. Suitable controls were maintained in each case. The seed lots were kept in 700 gauge polythene bags and stored under ambient conditions. The samples were drawn at an interval of 30 days to observe the influence of neem products and TMTD on germination, seedling vigour and seed health of soybean seeds over 120 days of storage. Significant increase in seedling dry weight was observed in all the treatments after 30 days of storage, with a marginal increase for TMTD treatment, and a more pronounced increase for neem products treated seeds vis-a-vis associated decline in the vigour of untreated seeds. In all the cultivars, MESK, HESK and MESC at 0.25 concentrations proved effective in controlling the associated mycoflora.